2017
DOI: 10.1007/s13202-017-0405-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequence stratigraphic approach to hydrocarbon exploration: a case study of Chiadu field at eastern onshore Niger Delta Basin, Nigeria

Abstract: This study integrated lithofacies, foraminifera and seismic data to develop a sequence stratigraphic approach to hydrocarbon exploration for Chiadu field. The application of lithostratigraphic approach led to correlation of diachronous lithofacies and wrongly defined an approximately accurate extent of the reservoirs. This study necessitated the use of sequence stratigraphic framework for the purpose of establishing chronostratigraphic concept and facies prediction. The genetic sequence model of Galloway was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The ancient redox conditions are mainly related to the content of free oxygen in the lake water, and the redox properties of the water are mainly characterized by the ratio of V/(V + Ni), Ni/Co and U/Th elements (Flemming, 2000; Nwaezeapu et al, 2018). The V/(V + Ni) ratios of this sample all ranged from 0.69 to 0.76, with an average of 0.73.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ancient redox conditions are mainly related to the content of free oxygen in the lake water, and the redox properties of the water are mainly characterized by the ratio of V/(V + Ni), Ni/Co and U/Th elements (Flemming, 2000; Nwaezeapu et al, 2018). The V/(V + Ni) ratios of this sample all ranged from 0.69 to 0.76, with an average of 0.73.…”
Section: Resultsmentioning
confidence: 99%
“…In the sequence framework, fine‐grained sediments often develop in the transgressive system tract (TST) or the early highstand system tract (LHST) and have different differences in different system tracts. The lithofacies characteristics (Cather et al, 2021; Lapidus, Kerimov, Mustaev, Movsumzade, & Zakharchenko, 2018; Leven, 2013; Nwaezeapu et al, 2018; Zhang, Bai, Jin, & Wang, 2016). Hemmesch, Harris, Mnich, and Selby (2014) studied the distribution characteristics of the minerals and lithofacies of the Woodford Shale in the Permian Basin and found that the high stand system tract (HST) developed mudstone and carbonate interbeds, and the TST developed organic‐rich shale (Hemmesch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time during recent years new approaches to the use of the sequence-stratigraphy method have been proposed by many researchers (Abd Al-Salam Al-Masgari et al, 2021;Ainsworth, 2010;Miller et al, 2018;Nwaezeapu et al, 2018;Okpikoro and Olorunniwo, 2010;Zhu et al, 2013). In the work by Abd Al-Salam Al-Masgari et al, sequence-stratigraphic research was carried out mainly on the basis of seismic data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One more new sequence-stratigraphy approach was suggested by Nwaezeapu et al According to this approach, the high-resolution biostratigraphy, analysis of logging diagrams and interpretation of seismic data are three major components making up the sequence-stratigraphy. All these data were analyzed and combined in order to decrease the uncertainty during correlation and mapping of sequences and system tracts (Nwaezeapu et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nwaezeapu et al presented that the electrofacies established on well logs correlate well with the sedimentary facies from core analysis, and the electrofacies established on well logs can be used to directly interpret the pale environments of the well formation [14].…”
Section: Well Log Facies Analysis and Associated Depositional Environmentioning
confidence: 99%